2018
DOI: 10.1016/j.jhsa.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Finger Replantation Optimization Study (FRONT): Update on National Trends

Abstract: Purpose: Traumatic digit amputations have an adverse impact on patients’ daily living. Despite experts advocating for digit replantation, studies have shown a continued decrease in rate of replantation. We performed a national-level investigation to examine the recent trend of practice for digital replantation. Methods: We used the National Inpatient Sample database under the Healthcare Cost and Utilization Project to select adult patients with traumatic digit amputation from 2001 to 2014.We calculated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
(35 reference statements)
5
41
1
2
Order By: Relevance
“…An interesting finding in the Cho et al [2] study was that patients with private insurance were twice as likely to receive replantation in comparison to patients with Medicare or Medicaid. As payer status directly influences reimbursement, they suggested that financial incentive may play a role.…”
Section: In Practice: Dwindling Interest and Attemptsmentioning
confidence: 94%
See 2 more Smart Citations
“…An interesting finding in the Cho et al [2] study was that patients with private insurance were twice as likely to receive replantation in comparison to patients with Medicare or Medicaid. As payer status directly influences reimbursement, they suggested that financial incentive may play a role.…”
Section: In Practice: Dwindling Interest and Attemptsmentioning
confidence: 94%
“…Their proposed solution was centralization of replantations. In distinction to this, Cho et al [2] found that "neither hospital case volume nor hospital type was predictive of successful replantation". Replantation attempts decreased at all hospital types: rural or urban, teaching or non-teaching.…”
Section: In Practice: Dwindling Interest and Attemptsmentioning
confidence: 95%
See 1 more Smart Citation
“…Los mecanismos de amputación contusivos y avulsivos son los más frecuentes, siendo el mecanismo por aplastamiento menos frecuente. 3 El mecanismo de guillotina, a pesar de ser la técnica más favorable y funcional, apenas ocurre. El mecanismo lesional por sí solo no contraindica la cirugía, pero nos informa sobre la dificultad técnica del reimplante, las posibles complicaciones y futuro resultado funcional (►Tabla 2).…”
Section: Mecanismos De Amputación Lesión Vascular E Indicación De Reunclassified
“…1 La atención en centros de referencia para esas lesiones presenta mayor tasa de indicación del reimplante, mayor éxito en la cirugía reparadora, disminución de los tiempos de ingreso hospitalario, menor coste económico y mayor planificación de procedimientos secundarios. [2][3][4] El dominio de las técnicas microquirúrgicas permite indicar el reimplante disminuyendo de forma notable las secuelas por amputación, a la vez que aumenta la satisfacción de los pacientes con el tratamiento recibido. [5][6][7] Es fundamental no confundir el éxito de las anastomosis vasculares con el éxito del resultado funcional.…”
unclassified